2013
DOI: 10.1183/09031936.00126712
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea, sleepiness, inflammation and insulin resistance in middle-aged males and females

Abstract: In obese males obstructive sleep apnoea (OSA) is associated with inflammation and insulin resistance; however, findings are confounded by adipose tissue, a hormone-and cytokine-secreting organ. Our goal was to examine whether in a relatively nonobese population, OSA is associated with sleepiness and inflammation/insulin resistance, and to assess the effects of a 2-month placebo-controlled continuous positive airway pressure (CPAP) use.77 subjects, 38 middle-aged males and post-menopausal females with OSA and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 51 publications
6
78
2
5
Order By: Relevance
“…Finally, patients with apnoea had significantly higher BDI-II scores, but their BAI scores were not significantly different. Similarly to what we have previously reported [18,19], apnoeic women had significantly higher BDI-II scores than their controls, while no differences in BDI-II or BAI scores between apnoeic and control men were observed. However, it should be noted that due to our inclusion criteria, BDI-II scores were very low, and thus not indicative of clinical depression for both apnoeics and controls.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Finally, patients with apnoea had significantly higher BDI-II scores, but their BAI scores were not significantly different. Similarly to what we have previously reported [18,19], apnoeic women had significantly higher BDI-II scores than their controls, while no differences in BDI-II or BAI scores between apnoeic and control men were observed. However, it should be noted that due to our inclusion criteria, BDI-II scores were very low, and thus not indicative of clinical depression for both apnoeics and controls.…”
Section: Resultssupporting
confidence: 88%
“…A thorough medical assessment, including history, physical examination, routine laboratory tests and sleep history, was completed for each participant as described in more detail above [18,19]. Anthropometric parameters were obtained and BMI was calculated based on height and weight measured as part of the physical examination.…”
Section: Sleep Laboratorymentioning
confidence: 99%
See 2 more Smart Citations
“…One of them was randomized clinical trial (RCT) [19], the remaining studies were observational [20][21][22][23][24][25][26][27][28][29]. One study [27] reported results separately for obese group and non-obese group.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%